Investigation on Anti-diabetic Efficacy of a Cucurbitaceae Food Plant from the North-East Region of India: Exploring the Molecular Mechanism through Modulation of Oxidative Stress and Glycosylated Hemoglobin (HbA1c) - Jana, Sandipan; Gayen, Srijon; Das Gupta, Barun; Singha, Seha; Mondal, Jayashree; Kar, Amit; Nepal, Abhimanyu; Ghosh, Suparna; Rajabalaya, Rajan; David, Sheba R.; Balaraman, Ashok K.; Bala, Asis; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: The medicinal plants of the Cucurbitaceae family, such as Solena heterophylla Lour. fruits, have significant ethnobotanical value and are readily accessible in North East India. Aims: We conducted a study on Solena heterophylla Lour. fruits to evaluate their anti-diabetic activity in vivo, standardize their HPTLC, and profile their metabolites using LC-QTOF-MS. We aimed to explore the molecular mechanism behind their effects on oxidative stress and glycosylated hemoglobin (HbA1c). Methods: Firstly, the ethyl acetate fraction of Solena heterophylla Lour. fruits was standardized using Cucurbitacin B as a standard marker by conducting HPTLC evaluation. Next, we delved into analyzing metabolite profiling. In addition, the standardized fraction was utilized in an experimental study to investigate the molecular mechanism of action in an in vivo high-fat diet and a low dose of streptozotocin-induced diabetic model. Results: We have reportedly identified 52 metabolites in the ethyl acetate fraction of Solena heterophylla (EASH). In the in vitro tests, it has been observed that this extract from plants possesses notable inhibitory properties against α-amylase and α-glucosidase. Solena heterophylla fruits with high levels of Cucurbitacin B (2.29% w/w) helped lower FBG levels in animals with EASH treatment. EASH treatment reduced HbA1c levels and normalized liver lipid peroxidation and antioxidant enzyme levels. SGOT, SGPT, and SALP serum enzyme levels also returned to normal. Conclusion: Based on the current evaluation, it was found that EASH exhibited encouraging hypoglycemic effects in diabetic rats induced by a low dose of STZ and high-fat diet, which warrants further investigation.
Keywords: anti-diabetic activity